2021
DOI: 10.1002/2211-5463.13097
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable reference genes for studies of Syringa pinnatifolia Hemsl.

Abstract: Syringa pinnatifolia Hemsl. (Oleaceae) is a species of shrub with a limited distribution in China. Several chemical compounds with pharmacological effects have been isolated from S. pinnatifolia, including new lignans and sesquiterpenes. Studies of gene expression in this species require the identification of suitable reference genes that are stably expressed under different conditions and in different tissues. To identify candidate reference genes, here we used the geNorm, NormFinder, and BestKeeper algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…It should be clear that the factors influencing the development and metabolism of plants, such as light, temperature, soil, and humidity, affect the expression of HMGR in S. pinnatifolia . Our previous study showed that low temperatures increase HMGR expression in S. pinnatifolia [ 68 ]. In the present study, the interaction of metabolite characteristics and the expression of some typical genes associated with plant immunity suggested that biotic stimulus, including pathogens and bacteria as referred to in a previous study [ 65 ], would be a potential and feasible approach to accelerate the accumulation of sesquiterpenes and lignans in the cultivation of S. pinnatifolia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be clear that the factors influencing the development and metabolism of plants, such as light, temperature, soil, and humidity, affect the expression of HMGR in S. pinnatifolia . Our previous study showed that low temperatures increase HMGR expression in S. pinnatifolia [ 68 ]. In the present study, the interaction of metabolite characteristics and the expression of some typical genes associated with plant immunity suggested that biotic stimulus, including pathogens and bacteria as referred to in a previous study [ 65 ], would be a potential and feasible approach to accelerate the accumulation of sesquiterpenes and lignans in the cultivation of S. pinnatifolia .…”
Section: Discussionmentioning
confidence: 99%
“…There were four biological repeats in the qRT-PCR, each with three technical repeats. Detailed information on the primers is provided in Supplementary Table S9, and TBP was chosen as the reference gene based on a previous study [ 68 ]. Gene expression was calculated using the 2 −ΔΔCT method [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…Stems were collected from both wild and cultivated S. pinnatifolia at Xiazi Gully in Mount Helan Nature Reserve (N38°29′32″, E105°50′2″) and the cultivation base of Alashan Mongolian Hospital in Alashan East Banner of Alashan (N38°58′41″, E105°54′7″), respectively, both located in Inner Mongolia, China. Potted S. pinnatifolia and calli, the latter induced according to the previously proposed method, [16] were cultivated in the phytotron at the National Resource Center for Chinese Materia Medica, China Academy of Chinese Medical Sciences, Beijing, China.…”
Section: Methodsmentioning
confidence: 99%
“…This endemic Chinese species is predominantly distributed in the upland of Helan Mountain, which is located between Ningxia and Inner Mongolia . Under the stress of high altitude, low temperature, drought, and other special abiotic factors in this area, S. pinnatifolia has produced compounds that are different from other plants in this genus. Previous phytochemical studies of S. pinnatifolia have reported the lignans, sesquiterpenoids, iridoid, and volatile oil, , and our group also has discovered a series of sesquiterpenes, including new skeletons of racemates by using 1 H NMR and LC-MS-guided methods. However, some signals indicating the presence of alkaloids caught our attention when analyzing the LC-MS data. Therefore, under the guidance of LC-MS, three quinone-terpenoid alkaloids were isolated from this species for the first time, namely alashanines A–C ( 1 – 3 ), as shown in Figure .…”
Section: Introductionmentioning
confidence: 95%